Thiostrepton interacts covalently with Rpt subunits of the 19S proteasome and proteasome substrates. Issue 9 (30th May 2015) - Sandu, Cristinel; Chandramouli, Nagaranjan; Glickman, Joseph Fraser; Molina, Henrik; Kuo, Chueh‐Ling; Kukushkin, Nikolay; Goldberg, Alfred L.; Steller, Hermann
Abstract Here, we report a novel mechanism of proteasome inhibition mediated by Thiostrepton (Thsp), which interacts covalently with Rpt subunits of the 19S proteasome and proteasome substrates. We identified Thsp in a cell‐based high‐throughput screen using a fluorescent reporter sensitive to degradation by the ubiquitin–proteasome pathway. Thiostrepton behaves as a proteasome inhibitor in several paradigms, including cell‐based reporters, detection of global ubiquitination status, and proteasome‐mediated labile protein degradation. In vitro, Thsp does not block the chymotrypsin activity of the 26S proteasome. In a cell‐based IκBα degradation assay, Thsp is a slow inhibitor and 4 hrs of treatment achieves the same effects as MG‐132 at 30 min. We show that Thsp forms covalent adducts with proteins in human cells and demonstrate their nature by mass spectrometry. Furthermore, the ability of Thsp to interact covalently with the cysteine residues is essential for its proteasome inhibitory function. We further show that a Thsp modified peptide cannot be degraded by proteasomes in vitro. Importantly, we demonstrate that Thsp binds covalently to Rpt subunits of the 19S regulatory particle and forms bridges with a proteasome substrate. Taken together, our results uncover an important role of Thsp in 19S proteasome inhibition.